APLIKASI ABSORBEN DAN FILTER CHITOSAN DARI LIMBAH CANGKANG KEPITING UNTUK MENINGKATKAN KUALITAS AIR YANG MENGANDUNG LOGAM BERAT - Ngadino .; Koerniasari . (GEMA LINGKUNGAN KESEHATAN, 2014)
Chitosan is a natural polymer derived from crab shell waste through a process of deproteination,demineralization, and deacetylation. Chitosan reported to be an effective adsorbent to remove someheavy metals. The main objective of this study is to evaluate the effectiveness of chitosan from crab shellwaste as an adsorbent and filter for increase water quality that contain heavy metals such as mercury(Hg) and lead (Pb). This experimental involved the determination of the adsorption and filter of chitosanfor mercury and lead ion. It was used solution of 500 mg/L lead and 1 mg/L mercury and was addedchitosan 0 %/ 2 % and 4 %. Then the mixture was continuously stirred using magnetic stirrer for 1hours at room temperature. After that solution was filtered and filtrate were analyzed using atomicadsorption spectroscopy to determine amount of lead and mercury adsorbed by chitosan. The resultindicated that the adsorption capacity of chitosan depends strongly on concentration of chitosan and onthe species of metallic ions in the water. The adsorption capacity for the mercury on chitosan was lowerthan lead. Chitosan, a type of biopolymer, is a good adsorbent to remove various kinds of heavy metalions. Chitosan has the highest adsorption capacity for mercury and lead ions because they have functionalgroups such as hydroxyls and amines which can bind mercury and lead ions. This chitosan can be a goodcandidate as adsorbent for adsorption of not only mercury and lead ions but also other heavy metal ions inwater.